Quality evaluation, fatty acid analysis and untargeted profiling of volatiles in Cambodian rice. (1st February 2018) - Concepcion, Jeanaflor Crystal T.; Ouk, Sothea; Riedel, Arthur; Calingacion, Mariafe; Zhao, Dule; Ouk, Makara; Garson, Mary J.; Fitzgerald, Melissa A.
Highlights: The set of Cambodian rice varieties is diverse in grain quality traits. Peak viscosity and breakdown are promising selection tools that indicate desired sensory texture. Fragrant varieties were highly characterised by N-containing volatiles based on GC × GC-TOF-MS. Possible fatty acid oxidation volatile products were more abundant among the fragrant varieties. Abstract: This study provides the first investigation of the physical traits, pasting properties and volatile compounds of Cambodian rice cultivars, including traditional, improved, and improved traditional varieties, allowing for their differentiation as high and low quality rice. Analysis of the grain quality traits illustrates interesting features of traditional varieties and correlations between traits that assist with understanding texture. Untargeted profiling of volatile compounds shows that high quality fragrant varieties not only contain 2-acetyl-1-pyrroline but also several other compounds, including aldehydes, alcohols and 2-alkylfurans that contribute to overall aroma. Moreover, low odour threshold volatile compounds, which can be derived from the oxidation of unsaturated fatty acids, were more abundant in the fragrant varieties. The percentage area of both oleic and linoleic acid were found to be significantly different among the rice varieties tested. Such findings suggest that unsaturated fatty acids in milled rice contribute to rice fragrance, and thereby to overall quality.